النظام القانوني للمجلس الأعلى للقضاء في الدستور الجزائري - جبالي ،عبد العالي (جامعة الوادي University of El Oued, 2024)
إن المجلس الأعلى للقضاء عبارة عن مؤسسة دستورية أنشأت من أجل تعزيز إستقلالية السلطة القضائية وتكريس مبدأ الفصل بين السلطات حيث نظمته العديد من النصوص القانونية وظيفتها حماية القضاة من كل أشكال التعسف والتدخل من المسار المهني للقضاة من طرف السلطة التنفيذية ومن خلال التشكيلة السابقة نلاحظ الأغلبية الساحقة المكونة للمجلس الأعلى للقضاء تمثل في الجهاز التنفيذي فقد عرف المجلس الأعلى للقضاء تغيير في تشكيلته حرصا على ملائمتها مع مختلف المتطلبات التي فرضتها المراحل المتغيرة في الجزائر، ثم جاء القانون العضوي رقم 22 -12 المتعلق بتشكيلة المجلس الأعلى للقضاء والقانون العضوي رقم 11-04 المتضمن القانون الأساسي للقضاء اللذان كرسا مبدأ إستقلالية القضاء، وللمجلس الأعلى صلاحية تأديب القضاة عقد إجتماعية كهئية تأديبية فهو يتخذ كل الاجراءات التأديبية في حالة إرتكاب القاضي خطأ من الأخطاء المهنية وذلك بتحديد عقوبات تأديبية ضمن أربع درجات وكان الإحالة على التعاقد التلقائي والعزل أقصى تلك العقوبات التي يوجهها القاضي خلال مساره المهني كما اعطى ضمانات اساسية تكفل الحماية للقاضي من كل متابعة تأديبية لأننا إذا بحثنا عن الغرض الحقيقي من فرض هذه السلطة التأديبية والتحكم بمسار المهني للقضاة من الناحية العضوية على المجلس الأعلى للقضاء من السلطة التنفيذية سنجد نية المشرع تتمثل في التحكم في وظيفة القضاة وجعلهم يختمون سياسة الطبقة الحاكمة. The Supreme Judicial Council is a constitutional institution established in order to strengthen the independence of the judiciary and establish the principle of separation of powers. It was organized by many legal texts. Its function is to protect judges from all forms of arbitrariness and interference in the professional career of judges by the executive authority. Through the previous composition, we notice the overwhelming majority composed of The Supreme Judicial Council is represented in the executive branch. The Supreme Judicial Council underwent a change in its composition in order to ensure its compatibility with the various requirements imposed by the changing stages in Algeria. Then came Organic Law No. 22-12 relating to the composition of the Supreme Judicial Council and Organic Law No. 11-04 containing the Basic Law. The judiciary has established the principle of independence of the judiciary, and the Supreme Council has the authority to discipline judges. It has a social contract as a disciplinary body. It takes all disciplinary measures in the event that a judge commits a professional error by determining disciplinary penalties within four levels. Referral to automatic contracting and dismissal is the maximum of those penalties that the judge directs during his course. The professional also gave basic guarantees guaranteeing protection for the judge from all disciplinary follow-up, because if we search for the real purpose of imposing this disciplinary authority and controlling the professional career of judges from an organic standpoint on the Supreme Judicial Council from the executive authority, we will find the legislator’s intention is to control the function of judges and make them stamp the class policy. The ruler.
ماستر اداري